Cinnamaldehyde constituent and screening of antibacterial potential in local Cinnamomum Zeylanicum bark / Zainab Razali, Nor Azira Irma Muhammad and Siti Nurwajihah Mohd Salleh - Razali, Zainab; Muhammad, Nor Azira Irma; Mohd, Siti Nurwajihah (Universiti Teknologi MARA, Perlis, 2016)
Cinnamomum belongs to the Lauraceae family which is an imperative traditional herbal medicine that is widely distributed all over the world. Our study aimed to identify the cinnamaldehyde constituent and investigate the antibacterial potential in local Cinnamomum zeylanicum bark. The bark was extracted in Petroleum ether using soxhlet apparatus and separatory evaporator until essential oil of C. zeylanicum bark was produced. Essential oil was injected into the Gas Chromatography and Mass Spectroscopy (GC-MS). Two gram positive culture Staphylococcus aureus, Bacillus subtilis and three gram negative culture which are Pseudomonas fluorescen, Salmonella typhimurium, and Serratia marcescens were used to test antibacterial activity using the agar disc diffusion method. Petroleum ether serves as negative control and tetracyline as positive control. From the results, S. typhimurium (44 mm) was found to be highly sensitive to it is action followed by P. fluorescen (35 mm), S. marcescen (34 mm), B. subtilis (33 mm), and S. aureus (29 mm) when the essential oil of C. zeylanicum had been applied on that bacteria cultures. These showed the antibacterial activity of the essential oil might be effect from cinnamaldehyde which found as major constituent in C. zeylanicum bark assist by other constituents could be potential as natural antibacterial agent in pharmaceutical industries.